Urgensi Pendirian Lembaga Keuangan Syariah (LKS) Wakaf Sebagai Upaya Mereduksi Kesenjangan Ekonomi di Indonesia (ZISWAF: Jurnal Zakat dan Wakaf, 2019)
Development is the government's effort to open jobs, suppress unemployment and alleviate poverty. Nevertheless, it is not easy to realize that glorious intention. Therefore, the role of society is indispensable. Islam offers solutions through Waqf and the potential waqf in Indonesia is quite large. Nevertheless, the role of BWI and Sharia financial institutions in Indonesia is currently not maximal. The purpose of this research is (1). Provide concepts, ideas and ideas through the establishment of Sharia financial institution (LKS) Waqf, especially cash waqf so that it becomes more productive and can reduce the economic gap (2). How to empower fundraising and increase trust in cash Waqf LKS. The research methodology is qualitative phenomenology. The result of the research that the financial institution form of Sharia Waqf is approaching the pillars and the requirement of Waqf is Sharia venture capital with minimal modifications in its operations. Therefore, the duties of the government, DSN, BWI, MUI and Islamic experts to further formulate the institution so that the management of the potential Waqf funds can be assembled and more productive to be channeled to the community and SMES.